The Teacher Performance Assessment: Reflections on the Pedagogical Thought Processes of Three Student Teachers - Kimberlee Anne Sharp (Arizona State University, 2010)
The impacts of the Teacher Performance Assessment (TPA) on 3 pre-service teachersâ pedagogical thought processes and self perceptions are the focus of this study. Qualitative research procedures included interviews, observations, and coding of the pre-service teachersâ written documents. Emerging themes and implications for teacher education include variance in: 1) the pre-service teachersâ ability to analyze and articulate learner outcome results; 2) how they thought they impacted student learning; and 3) their locus of control.